Filozoficzna apologia monofizytyzmu w "Rozjemcy" Jana Gramatyka - Mielnik, Dawid (Vox Patrum, 2020)
The main purpose of the paper is an attempt of presentation of philosophical argumentation used by ancient philosopher John Philoponus for justifying the condemned by Council of Chalcedon monophysical doctrine. The purpose realization was possible thanks to analysis of arguments used by Philoponus which arguments were presented in six chapters of his Arbiter. The paper was divided into three parts. In the first one the profile of Arbiter was presented. In the second one, which was longer in relation to volume, the philosopher’s systematic teaching was analyzed. In the last one the most important features of Philoponus’ argumentation were presented. On the basis of the analysis it could be claimed that John Philoponus used the terms “nature” and “substance” interchangeably. What’s more, he used different examples for showing the legitimacy of his reasoning and he also builds next arguments on the ground of beforehand conclusions.